The experience of translation : materiality and play in experiential translation - Campbell, Madeleine; Vidal, Ricarda (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Campbell, Vidal and their contributors expand the notion of translation beyond linguistic, modal and medial borders to embrace posthumanist perspectives through a holistic experiential epistemology which envisions translation as engaged, situated social practice. The first of two volumes, this book focuses on questions of materiality and play. Drawing together contributions on theory, methodology and practice from translators, scholars and practitioners working in the creative and performing arts, this book explores how contemporary, experiential acts of interpretation, mediation and negotiation can serve to bridge social and cultural discontinuities across time and space. These range from ancestral past to digital present, from rural to urban environments across the globe. Experiential translation applies a transdisciplinary lens to problematize views of translation and untranslatability traditionally bound by structuralist frames of reference and the reserve of professional linguistic translation. The chapters in this book apply this experiential lens to understand a pluriverse of creative translation practices where the translator's subject position in relation to the 'original' is transformed by the role of experimentation, creativity and play. This book and its companion volume The Translation of Experience: Cultural Artefacts in Experiential Translation will be of particular interest to translators and arts practitioners, scholars and researchers in the transdisciplinary field of humanities"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Madeleine Campbell teaches at Edinburgh University. Her transdisciplinary publications span arts-informed language education, experiential translation and creativity, including Translating across Sensory and Linguistic Borders (2019) and 'The multimodal translation workshop as a method of creative inquiry--acousmatic sound, affective perception and experiential literacy' (forthcoming in Target). She is Co-Investigator of the AHRC-funded Experiential Translation Network (ETN). Profile: https://www.researchgate.net/profile/Madeleine-Campbell/publications Ricarda Vidal is Senior Lecturer at King's College London and Principal Investigator of the AHRC-funded Experiential Translation Network. As researcher, text-maker and curator, she explores the multimodal aspects of communication across perceived cultural and/or linguistic divides. Recent publications include Translating across Sensory and Linguistic Borders (2019), Home on the Move (2019) and the bookwork series Revolve:R (2011-2023). Profile: https://kclpure.kcl.ac.uk/portal/en/persons/ricarda.vidal/publications
Added to collection customer.56279.3
Keywords: Translating and interpreting; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / General; Essays